Analysis of the 2021 Bundestag elections. 2/4. Political spectrum - Andranick S. Tanguiane (Karlsruher Institut für Technologie (KIT), Institut für Volkswirtschaftslehre (ECON), 2022)
This is the second out of four papers devoted to the 2021 German federal elections continuing our analysis of the 2009, 2013 and 2017 Bundestag elections. This paper arranges the contesting parties into a 'spectrum' that reflects the spatial proximity of their policy profiles. The latter are 38-dimensional vectors of the parties' answers to 38 policy questions from the 2021 Wahl-O-Mat, the German voting advice application (VAA). Applying Principal component analysis (PCA), we construct a contiguous party ordering where the neighboring parties have close policy profiles. The ordering fits to the left-right ideological axis rolled up in a circumference, which can be unfolded by splitting it at one of its largest gaps. Rigorously speaking, we obtain a horseshoe-shaped left-right axis with the far-left and far-right ends approaching each other. For comparisons, alternative party orderings are constructed using four other models. Finally, the 2013, 2017 and 2021 German political spectra are compared.
Keywords: D71; 330; Policy representation; representative democracy; political spectrum; left-right ideological axis